2017
DOI: 10.1101/189332
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide Variants of Eurasian Facial Shape Differentiation and a prospective model of DNA based Face Prediction

Abstract: It is a long standing question as to which genes define the characteristic facial features among different ethnic groups. In this study, we use Uyghurs, an ancient admixed population to query the genetic bases why Europeans and Han Chinese look different. Facial traits were analyzed based on high-dense 3D facial images; numerous biometric spaces were examined for divergent facial features between European and Han Chinese, ranging from inter-landmark distances to dense shape geometrics. Genome-wide association … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 66 publications
0
13
1
Order By: Relevance
“…Anc refers to 1,000 genomic PCs. SNPs refers to previously reported SNPs related to facial structure (5,14,27). …”
Section: Significancementioning
confidence: 99%
“…Anc refers to 1,000 genomic PCs. SNPs refers to previously reported SNPs related to facial structure (5,14,27). …”
Section: Significancementioning
confidence: 99%
“…In fact, racial factors are a major cause because the results come from different populations, such as Europeans, Americans, Africans and East Asians, etc. (Adhikari et al 2016 ; Cha et al 2018 ; Claes et al 2018 ; Cole et al 2016 ; Lee et al 2017 ; Liu et al 2012 ; Paternoster et al 2012 ; Qiao et al 2018 ; Shaffer et al 2016 ). Even in the same race, such as in Europeans, few of the genes or loci identified in each study have been replicated (Adhikari et al 2016 ; Lee et al 2017 ; Paternoster et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The WinEDMA 1.0.1 software ( http://c.faculty.umkc.edu/colet ) was used to calculate the Euclidean distances between landmarks. The above-mentioned reports (Adhikari et al 2016 ; Cha et al 2018 ; Claes et al 2018 ; Cole et al 2016 ; Lee et al 2017 ; Liu et al 2012 ; Paternoster et al 2012 ; Qiao et al 2018 ; Shaffer et al 2016 ) concluded that gene loci of facial phenotypes were mostly associated with the shapes of the nose, mouth, and mandible, especially the nasal region. Therefore, this study selected phenotypes mostly from these regions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their abundant distribution in both the nuclear and mitochondrial genome, SNPs increasingly can provide the genetic background for the prediction of physical characteristics [200,201], or geographical origin [202,203], and can also provide investigative tools to trace unknown individuals [204,205] even from historical remains [206][207][208]. Determination of ancestry [209,210] and externally visible characteristics, such as skin, eye and hair pigmentation [211,212], morphology [213,214], or age [215,216], is an ongoing research field of forensics, requiring both forensic validation of analytical platforms and computation data.…”
Section: Markers For Supplemental Informationmentioning
confidence: 99%